2004
DOI: 10.1111/j.1440-6055.2003.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Spider fauna of soybean crops in south‐east Queensland and their potential as predators of Helicoverpa spp. (Lepidoptera: Noctuidae)

Abstract: Spiders are among the most abundant predators recorded in grain crops in Australia. They are voracious predators, and combined with their high abundance, may play an important role in the reduction of pest populations. The significance of spider assemblages as biological control agents of key pests such as Helicoverpa spp. in Australian agroecosystems is largely unknown. A thorough inventory was made of the spider fauna inhabiting unsprayed soybean fields at Gatton, south-east Queensland. Onehundred-and-two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…The pest's status (alive, killed or eaten) was recorded after every 4-h interval for 24 h. Dead pests were examined under an enlarging scope and compared their appearance to that of dead pests from the control containers. The nymphs killed by spiders appeared shriveled, which indicated that spiders were feeding on them (Pearce et al 2004). …”
Section: No Choice Feeding Tests In Laboratorymentioning
confidence: 97%
See 1 more Smart Citation
“…The pest's status (alive, killed or eaten) was recorded after every 4-h interval for 24 h. Dead pests were examined under an enlarging scope and compared their appearance to that of dead pests from the control containers. The nymphs killed by spiders appeared shriveled, which indicated that spiders were feeding on them (Pearce et al 2004). …”
Section: No Choice Feeding Tests In Laboratorymentioning
confidence: 97%
“…The dishes were examined after every 4-h interval for 24 h after the introduction of predator and the number of larvae dead or consumed was recorded. Control dishes (n = 10) containing ten larvae but no spider, were used to assess the number of larvae that died during same time (Pearce et al 2004). …”
Section: No Choice Feeding Tests In Laboratorymentioning
confidence: 99%
“…Natural enemies are the important component in the population dynamics of this butterfly. The natural enemies have influence on total insect number and some-times their impact is related to the density of their prey (Hirosie et al 1980;Watanabe 1981;Feeny et al 1985;Stefanescu 2000;Zalucki et al 2002;Pearce et al 2004;Nava et al 2005;Stefanescu et al 2006). .00* Note: L1 = first instar larvae; L2 = second instar larvae; L3 = third instar larvae; L4 = fourth instar larvae; L5 = fifth instar larvae; Significant values marked with an asterisk "*" are significantly different (Friedman test, P < 0.05) Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The most important predator, spider was well adapted to living on the same host plant with P. polytes larvae. On grain crop in Australia, Pearce et al (2004) reported that spiders were also among the most abundant predators. Since the spiders are voracious predators and combined with their high abundance, they played an important role in the reduction of the pest populations.…”
Section: B I O D I V E R S It a S 11 (1): 19-23 January 2010 22mentioning
confidence: 99%
“…the cursorial spiders Miturgidae or Salticidae). The activity of these cursorial spiders may be harnessed for the control of pests such as Lepidoptera, whose eggs and larvae cannot be captured in a web (Mansour, 1987;Pearce, Hebron, Raven, Zalucki, & Hassan, 2004;Pfannenstiel, 2008). Recently, Pérez-Guerrero et al (2013) reported that certain cursorial families (Miturgidae and Philodromidae) displayed greater potential predation on lepidopteran larvae than other hunting families (e.g.…”
Section: Introductionmentioning
confidence: 98%